Optimization design of neutrally buoyant hull for underwater gliders. (1st August 2020) - Yang, Ming; Yang, Shaoqiong; Wang, Yanhui; Liang, Yan; Wang, Shuxin; Zhang, Lianhong
Abstract: The net buoyancy, driving force of underwater gliders, decreases gradually when the gliders dive or climb in the seawater, which increases the energy consumption and reduces the gliding range. The neutrally buoyant hull is an effective measure to reduce this buoyancy loss of underwater gliders. In this paper, a multiple intersecting spheres (MIS) pressure hull is designed to provide neutral buoyancy. A mechanical model of the hull is established with the thin shell theory, based on which the optimization is carried out by combining the penalty function method (PFM) and multiple population genetic algorithm (MPGA). Thickness of the spherical shell, reinforcing rib, width of the reinforcing rib, and intersection angle of the spherical shell are optimized for minimizing the buoyancy factor which is defined as the ratio of pressure hull mass to the undeformed displacement. Additionally, the mechanical model is verified by the finite element analysis and the pressure test. The results show that the MIS pressure hull can increase the buoyancy compensation by 69.69% and increase battery capacity of the glider by 12.89% as compared with conventional cylindrical hull. This will improve the navigation range and duration of Petrel-L glider more obviously when its hotel load is lower. Highlights: A multiple intersecting spheres (MIS) pressure hull is optimized to provide neutral buoyancy. A mechanical model of the MIS pressure hull is established with the thin shell theory. An optimization is established to minimize the buoyancy factor. The MIS pressure hull can increase buoyancy compensation by 69.69% and increase battery capacityby 12.89%.